Blowback: The effect of sanctions on democratic elections - Matthieu Crozet; Julian Hinz (Kiel Institute for the World Economy (IfW Kiel), 2023)
Sanctions are meant to coerce political adversaries through economic measures. However, evidence for their effectiveness is scarce. In this paper we assess the impact of sanctions on a democracy - France - by studying the electoral consequences of the sanctions and countersanctions imposed between Russia and Western countries. Contrary to most of the existing literature we find clear evidence for exposure to the sanctions to cause an increase in the vote share for pro-Russian (and far-right) candidates during the French 2017 presidential election. Locally, the impact on voting is substantial. Back-of-the-envelope calculations indicate that about 16,300 votes for the main far-right candidate can be directly attributed to the sanctions' impact. This is the total number of votes cast in a medium-sized French city. It is however not nearly enough to have affected the outcome of the election at the national level.
Keywords: F13; F51; D72; D74; 330; Sanctions; Elections; Embargo; Russia; France